Foundations of political economy : some early Tudor views on state and society - Wood, Neal. (Berkeley : University of California Press, 1994)
Conventional wisdom claims that the seventeenth century gave birth to the material and ideological forces that culminated in the Industrial Revolution and the rise of capitalism. Not true, according to Neal Wood, who argues that much earlier reformers--Dudley, Starkey, Brinklow, Latimer, Crowley, Becon, Lever, and Thomas Smith, as well as the better-known More and Fortescue--laid the groundwork by fashioning an economic conception of the state in response to s.
Intro -- Contents -- Preface -- 1. INTRODUCTION: THE REFORMERS -- 2. EARLY SIXTEENTH-CENTURY ENGLAND -- 3. TOWARD AN ECONOMIC CONCEPTION OF THE STATE -- 4. FORERUNNER OF THE REFORMERS: SIR JOHN FORTESCUE -- 5. FIRST OF THE REFORMERS: SIR EDMUND DUDLEY -- 6. THE ENLIGHTENED CONSERVATIVE: SIR THOMAS MORE -- 7. LIFE OF DIGNITY IN THE ""TRUE COMMYN WELE"": THOMAS STARKEY -- 8. SOCIAL PROTEST AND CHRISTIAN RENEWAL: THE COMMONWEALTHMEN -- 9. SIR THOMAS SMITH'S NEW ""MORAL PHILOSOPHY -- 10. Conclusion -- Notes -- Index
Includes bibliographical references (pages 251-302) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Economics -- Great Britain -- History -- To 1800.; Political science -- Great Britain -- History -- 16th century; Économie politique -- Grande-Bretagne -- Histoire -- Jusqu'à 1800.; POLITICAL SCIENCE -- Public Policy -- Economic Policy; BUSINESS & ECONOMICS -- Government & Business; BUSINESS & ECONOMICS -- Development -- Economic Development; BUSINESS & ECONOMICS -- Development -- Business Development; BUSINESS & ECONOMICS -- Structural Adjustment; BUSINESS & ECONOMICS -- Development -- General; HISTORY / Europe / General; Economics; Political science; Great Britain; Economische filosofie; Politieke ideeën.; Verenigd Koninkrijk van Groot-Brittannië en Noord-Ierland.; Business & Economics; Economic Theory; To 1800; History